2018
DOI: 10.1111/ijsw.12364
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of South African caregivers in receipt of Child Support Grants: Implications for family strengthening interventions

Abstract: Cash transfers have delivered measurable benefits for poor and vulnerable children in low‐ and middle‐income countries. However, on its own, a cash transfer is insufficient to promote holistic child well‐being. In the quest for appropriate complementary family support services, known as ‘cash plus’ programing, this qualitative study sought to explore the perspectives of a group of South African caregivers, all of whom were in receipt of a Child Support Grant (CSG), in relation to their own caregiving and famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…This has created skipped generations and exerted pressure on both the orphaned grandchildren and the grandmothers as they both struggle to close the generation gap. To create some relief from critical poverty situations, the caregivers' income to support the orphaned children is mainly from social grants which in many South African communities is celebrated (Patel, Hotchfeld & Chiba, 2018). However, social grants are also criticised for creating dependence on the government and entrenching poverty on the part of the caregivers.…”
Section: Demographic Information Of Caregiversmentioning
confidence: 99%
See 1 more Smart Citation
“…This has created skipped generations and exerted pressure on both the orphaned grandchildren and the grandmothers as they both struggle to close the generation gap. To create some relief from critical poverty situations, the caregivers' income to support the orphaned children is mainly from social grants which in many South African communities is celebrated (Patel, Hotchfeld & Chiba, 2018). However, social grants are also criticised for creating dependence on the government and entrenching poverty on the part of the caregivers.…”
Section: Demographic Information Of Caregiversmentioning
confidence: 99%
“…However, social grants are also criticised for creating dependence on the government and entrenching poverty on the part of the caregivers. This source of income has proved also to be inadequate to meet the exorbitant needs of caring for orphans, hence other caregivers mitigate this by supplementing the grants through extra sources of income (Patel et al, 2018).…”
Section: Demographic Information Of Caregiversmentioning
confidence: 99%
“…Similar effects are attributed to CSG in a country where extreme poverty among women is prevalent, and higher female unemployment and lower wages have caused a widening gender poverty gap (Plagerson and Ulriksen, 2015: 11). Without CSG, “the single most significant poverty alleviation mechanism of the state” (Patel et al, 2019a: 307), the sizable share of female-headed households that survive on social grant income alone would be worse off (DSD et al, 2012). Moreover, ample evidence suggests that CSG income has been relatively more important in reducing the extent and depth of poverty among female- versus male-headed households.…”
Section: Economic Dimensions Of Empowermentmentioning
confidence: 99%
“… 27. When investigators in one study asked caregivers where they sought emotional and psychological support, they identified their family and church rather than professional sources like social workers (Patel et al, 2019a: 313). …”
mentioning
confidence: 99%
“…Research has indicated that social grants are crucial for the survival of poorer households, they are still insufficient for properly and sustainably moving people out of poverty [ 29 , 30 , 31 ]. Disability grants are around four times the amount of poverty-alleviation grants, but for most recipients, disability grants still do not meet their needs because of the very high costs associated with disability [ 8 , 32 ].…”
Section: Introductionmentioning
confidence: 99%